Psychometric Properties of the Chinese Version of the Intolerance of Uncertainty Inventory in Chinese College Students - Li S (Dove Medical Press, 2020)
Siya Li,1 Feilong Yang,2 Peihuan Li,1 Xiang Wang,3 Ji Dai,4 Yunlong Deng1,2 1Department of Clinical Psychology, The Third Xiangya Hospital, Central South University, Changsha, Hunan 410013, People’s Republic of China; 2Psychosomatic Health Institute, The Third Xiangya Hospital, Central South University, Changsha, Hunan 410013, People’s Republic of China; 3Medical Psychological Center, The Second Xiangya Hospital, Central South University, Changsha, Hunan 410011, People’s Republic of China; 4Mental Health Education Center, Hunan University of Technology and Business, Changsha, Hunan 410205, People’s Republic of ChinaCorrespondence: Yunlong DengDepartment of Clinical Psychology, The Third Xiangya Hospital, Central South University, No. 138 Tongzipo Road, Yuelu District, Changsha, Hunan 410013, People’s Republic of ChinaTel +86 18975186178Fax +86 731 88618487Email deng0087@126.comBackground: Intolerance of uncertainty (IU) is considered to be associated with emotional disorders, such as generalized anxiety disorder (GAD), depression, obsessive compulsive disorder (OCD), and social anxiety. Therefore, a comprehensive instrument to measure IU is needed. The purposes of the present study were as follows: 1) developing a Chinese version of the Intolerance of Uncertainty Inventory (CIUI) and 2) measuring the reliability and validity of CIUI.Methods: We translated the Intolerance of Uncertainty Inventory (IUI) into Chinese. A sample consisting of Chinese college students from three universities was used to evaluate the internal consistency, test–retest reliability, and validity of the CIUI. Participants answered the CIUI, IUS-12, GAD-7, BDI-II, and PSWQ. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were run to explore the factor structure of CIUI.Results: The results demonstrated an acceptable internal consistency for CIUI (Part A of CIUI [CIUIA]: α = 0.920; Part B of CIUI [CIUIB]: α = 0.947) and test–retest reliability (CIUIA: ICC = 0.788; CIUIB: ICC = 0.859). The results of EFA and CFA all supported a two-factor structure for CIUIA (Intolerance of the unexpected and difficulty waiting in an uncertain situation and Intolerance of uncertainty and of uncertain situations) and a four-factor structure for CIUIB (Overestimation, Control, Uncertainty makes one feel stressful, and Reassurance), and acceptable validity was obtained.Conclusion: The CIUI is an appropriate instrument for measuring IU in Chinese populations. Future studies should confirm the psychometric properties using a comprehensive sample.Keywords: intolerance of uncertainty, reliability, validity, Chinese population